Microsporum canis Complex Infections in the United Arab Emirates: Clinical, Molecular, and Antifungal Susceptibility Profiles - Febin Anes; Akela Ghazawi; Hari Pankaj Vanam; Dana Aljneibi; Mushtaq Khan; Fouzia Jabeen; Ahmed R Alsuwaidi; Jens Thomsen; Mohammad AlBataineh; Stefan Weber; Connie Gibas; Nathan P Wiederhold; et al. (Medical Mycology, 2026)
Abstract Microsporum canis complex infections remain a major cause of pediatric dermatophytosis, yet molecular epidemiologic and antifungal susceptibility data from the Arabian Gulf are scarce, with no contemporary regional assessment since 1981–1988. We characterized the clinical, molecular, and antifungal susceptibility profiles of M. canis complex isolates in Abu Dhabi and assessed concordance between phenotypic and ITS-based identification. Fifty-two clinical dermatophyte isolates collected through passive surveillance at the UAEU Fungal Reference Laboratory (September 2024–December 2025) underwent phenotypic identification, ITS sequencing, and antifungal susceptibility testing (CLSI M38). Clinical data were available for 48 patients. ITS sequencing identified 47 isolates (90.4%) as M. canis and 5 (9.6%) as the M. audouinii clade, with phenotypic discordance in 9.6% of isolates (including one M. canis misidentified as Trichophyton rubrum). The cohort was predominantly pediatric (79.2% ≤12 years; 54.2% female). Tinea capitis predominated (60.4%), followed by tinea corporis (20.8%) and multifocal disease (16.7%). Cat exposure was reported in 50% and infected household contact in 27.1%. All isolates showed low MICs (terbinafine MIC₅₀/₉₀ 0.015/0.03; itraconazole ≤0.03/0.06; voriconazole ≤0.03/≤0.03; griseofulvin 0.125/0.25; fluconazole 4/8 µg/mL). Despite this, 81.2% (26/32) of patients with follow-up experienced treatment failure or recurrence, with no clear MIC–outcome association. This first molecular and antifungal characterization of M. canis complex infections in the UAE over three decades showed that ITS sequencing corrected phenotypic identification in nearly 10% of cases. High recurrence despite low MICs suggests limited predictive value of in vitro susceptibility, supporting species directed management, molecular confirmation, species-directed management, and One Health strategies.